Identification and Analysis of NaHCO3 Stress Responsive Genes in Wild Soybean (Glycine soja) Roots by RNA-seq - Zhang, Jinlong; Wang, Jiaxue; Jiang, Wei; Liu, Juge; Yang, Songnan; Gai, Junyi; Li, Yan (Frontiers in Plant Science, 2016)
Soil alkalinity is a major abiotic constraint to crop productivity and quality. Wild soybean (Glycine soja) is considered to be more stress-tolerant than cultivated soybean (G. max), and has considerable genetic variation for increasing alkalinity tolerance of soybean. In this study, we analyzed the transcriptome profile in the roots of an alkalinity tolerant wild soybean variety N24852 at 12 and 24 h after 90 mM NaHCO3 stress by RNA-sequencing. Compared with the controls, a total of 449 differentially expressed genes (DEGs) were identified, including 95 and 140 up-regulated genes, and 108 and 135 down-regulated genes at 12 and 24 h after NaHCO3 treatment, respectively. Quantitative RT-PCR analysis of 14 DEGs showed a high consistency with their expression profiles by RNA-sequencing. Gene Ontology (GO) terms related to transcription factors and transporters were significantly enriched in the up-regulated genes at 12 and 24 h after NaHCO3 stress, respectively. Nuclear Factor Y subunit A (NF-YA) transcription factors were enriched at 12 h after NaHCO3 stress, and high percentages of basic helix-loop-helix (bHLH), ethylene-responsive factor (ERF), Trihelix and zinc finger (C2H2, C3H) transcription factors were found at both 12 and 24 h after NaHCO3 stress. Genes related to ion transporters such as ABC transporter, aluminum activated malate transporter (ALMT), glutamate receptor (GLR), nitrate transporter (NRT) / proton dependent oligopeptide (POT) family, and S-type anion channel (SLAH) were enriched in up-regulated DEGs at 24 h after NaHCO3 treatment, implying their roles in maintaining ion homeostasis in soybean roots under alkalinity. KEGG pathway enrichment analysis showed “phenylpropanoid biosynthesis” and “phenylalanine metabolism” pathways might participate in soybean response to alkalinity. This study provides a foundation to further investigate the functions of NaHCO3 stress-responsive genes and the molecular basis of soybean tolerance to alkalinity.